2013
DOI: 10.1016/j.clinph.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of early cortical auditory gamma-band responses

Abstract: Objective To evaluate the test-retest reliability of event-related power changes in the 30–150 Hz gamma frequency range occurring in the first 150 ms after presentation of an auditory stimulus. Methods Repeat intracranial electrocorticographic (ECoG) recordings were performed with 12 epilepsy patients, at ≥ 1-day intervals, using a passive odd-ball paradigm with steady-state tones. Time-frequency matching pursuit analysis was used to quantify changes in gamma-band power relative to pre-stimulus baseline. Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 68 publications
(139 reference statements)
0
20
0
Order By: Relevance
“…The peak in the spectrum (the frequency for which the amplitude is largest in the time frequency analysis) is highly variable across individuals, but at the same time, relatively constant within individuals (Fründ et al, 2007). Cervenka et al (2013) found early cortical auditory eGBRs to be test-retest reliable, regardless of general individual auditory performance. The same stability has been revealed for the preferred frequency of the auditory cortex (Baltus and Herrmann, 2015).…”
Section: Resonance Frequencies Of the Auditory Cortex And Higher Areasmentioning
confidence: 91%
“…The peak in the spectrum (the frequency for which the amplitude is largest in the time frequency analysis) is highly variable across individuals, but at the same time, relatively constant within individuals (Fründ et al, 2007). Cervenka et al (2013) found early cortical auditory eGBRs to be test-retest reliable, regardless of general individual auditory performance. The same stability has been revealed for the preferred frequency of the auditory cortex (Baltus and Herrmann, 2015).…”
Section: Resonance Frequencies Of the Auditory Cortex And Higher Areasmentioning
confidence: 91%
“…We computed the time-frequency energy distribution of ictal activity in all recorded channels using a matching pursuit (MP) algorithm (Mallat and Zhang, 1993), which has been previously successfully used for detection of epileptic activity (Jouny et al, 2007a; Jouny et al, 2003), as well as functional activity (Boatman-Reich et al, 2010; Cervenka et al, 2011a; Cervenka et al, 2013a; Cervenka et al, 2013b; Cervenka et al, 2011b). MP is an iterative procedure that decomposes signal x(t) into a linear combination of members of a specified set of functions.…”
Section: Methodsmentioning
confidence: 99%
“…ECoG recordings are characterized by high signal-to-noise ratios and excellent temporal (1-2 ms) and spatial (10 mm) resolution. ECoG recordings from the human auditory cortex have been shown recently to be highly reliable and reproducible (Cervenka et al , 2013). Resting on the unique properties of the ECoG, below we propose a new dynamic directional model (DDM) with a simple formulation to evaluate the effective connectivity between many brain components.…”
Section: Directional Dynamical Modelmentioning
confidence: 99%
“…Event-related ECoG recordings were acquired simultaneously from all electrodes using an established 300-trial passive auditory oddball paradigm (Sinai et al , 2009; Cervenka et al , 2013). Two 50 ms duration single-frequency tones were presented: a frequently repeated 1000 Hz tone ( N =246 trials) and an infrequently and pseudo-randomly presented (no consecutive repetitions) 1200 Hz tone ( N =54 trials).…”
Section: Application To a Real Ecog Studymentioning
confidence: 99%
See 1 more Smart Citation